Comprehensive Physiology 1998
DOI: 10.1002/cphy.cp070118
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/Paracrine Intermediates in Hormonal Action and Modulation of Cellular Responses to Hormones

Abstract: The sections in this article are: Methods to Explore Local Control Local Control in the Anterior Pituitary Evidence for Intercellular Communication in the Anterior Pituitary Putative Paracrine Factors Local Control in the Adrenal Cortex and Medulla Morphological Correlates of Medulla–Cortex Interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 646 publications
2
8
0
Order By: Relevance
“…Therefore, the present study shows that the lactating rat pituitary produces PRL variants that are absent or deficient in the male pituitary gland and in the PRL Standard, even though the AP of male and of other types of rats, do respond to stimulatory factors released from the anterior pituitary of lactating rats (Mena et al, 2010). The results presented here, together with those in our previous study, also indicate that several PRL variants are produced and released by the lactating rat pituitary (Denef, 1988;Sinha 1992;Asawaroengchai et al, 1978); this hormonal heterogeneity may be physiologically very relevant in the context of autoregulatory mechanisms determining the wide range of PRL effects under different physiological conditions (Schwartz & Cherny, 1992;Schwartz, 2000;Sinha, 1992) and upon different structures (Ben-Jonathan et al, 2001;Lorenson & Walker, 2001;Ho et al, 1993;Celotti et al, 1997).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, the present study shows that the lactating rat pituitary produces PRL variants that are absent or deficient in the male pituitary gland and in the PRL Standard, even though the AP of male and of other types of rats, do respond to stimulatory factors released from the anterior pituitary of lactating rats (Mena et al, 2010). The results presented here, together with those in our previous study, also indicate that several PRL variants are produced and released by the lactating rat pituitary (Denef, 1988;Sinha 1992;Asawaroengchai et al, 1978); this hormonal heterogeneity may be physiologically very relevant in the context of autoregulatory mechanisms determining the wide range of PRL effects under different physiological conditions (Schwartz & Cherny, 1992;Schwartz, 2000;Sinha, 1992) and upon different structures (Ben-Jonathan et al, 2001;Lorenson & Walker, 2001;Ho et al, 1993;Celotti et al, 1997).…”
Section: Discussionsupporting
confidence: 83%
“…The synthesis and release of prolactin (PRL) by lactotrophs in the anterior pituitary (AP) are regulated by factors produced in the hypothalamus as well as in the posterior and neurointermediate pituitary lobes, by autocrine and paracrine signals from the anterior pituitary itself (Ben-Jonathan & Hnasko, 2001;Kordon, 1985;Denef, 1988;Denef, 2008;Freeman et al, 2000;Lorenson and Walker, 2001;Schwartz & Cherny, 1992;Schwartz, 2000;Wang & Walker, 1993;Sinha, 1992;Sinha 1995;Moore et al, 2002;Bollengier et al, 1989;Bollengier et al, 1996;Kadowaki et al, 1984;MacLeod et al, 1966;Sgouris & Meites, 1953;Chen et al, 1968;Welsch et al, 1968) and also by gonadal steroids (Maurer & Gorski, 1977;Maurer, 1982). In addition, it has been reported that total PRL and PRL variants (Denef, 2008;Shah & Hymer, 1989) are secreted under different physiological conditions (Denef, 2008;Wang & Walker, 1993;Sinha, 1992;Sinha 1995;Mena et al, 1984;Mena et al, 1992;Boockfor & Frawley, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that total PRL and PRL variants are secreted under different physiological conditions (3)(4)(5)(6)(7)(8) and it is known that functional interactions and cytological differences exist among pituitary lactotrophs within the anterior pituitary gland (2)(3)(4)(5)(6)(7) and that functional variations (8)(9)(10), as well as autoregulation (11)(12) and interactions with other pituitary cells (3,7,9) and with hypothalamic hormones (1,3,9) occur in different circumstances. For instance, lactotrophs from the central AP region (CR) of lactating rats, i.e., the region surrounding the neurointermediate pituitary lobe are bigger (10,13), secrete more PRL than those of the peripheral AP region (PR) and after a short period of suckling become more sensitive to the PRL-stimulatory agents, TRH and angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and release of prolactin (PRL) by lactotrophs in the anterior pituitary (AP) are regulated by factors produced in the hypothalamus as well as in the posterior and neurointermediate pituitary lobes, by autocrine and paracrine signals from the anterior pituitary itself (for review see [1][2][3][4][5]. In addition, it has been reported that total PRL and PRL variants are secreted under different physiological conditions (3)(4)(5)(6)(7)(8) and it is known that functional interactions and cytological differences exist among pituitary lactotrophs within the anterior pituitary gland (2)(3)(4)(5)(6)(7) and that functional variations (8)(9)(10), as well as autoregulation (11)(12) and interactions with other pituitary cells (3,7,9) and with hypothalamic hormones (1,3,9) occur in different circumstances.…”
Section: Introductionmentioning
confidence: 99%